Utilization of distal radius and ulna classification scheme in predicting growth peak and curve progression in idiopathic scoliosis girls undergoing bracing treatment - Li, Yang; Mao, Saihu; Shi, Bo; Liu, Zhen; Liu, Dun; Sun, Xu; Qiu, Yong; Zhu, Zezhang (European spine journal, 2020)
Purpose Distal radius and ulna (DRU) classification scheme has been proposed for predicting skeletal maturity in patients with idiopathic scoliosis (IS). However, the utilization of DRU classification scheme in the assessment of growth peak and curve progression in IS was still inconclusive. This study aimed to correlate the distal radius and ulna stages with several indicators for growth potential and to evaluate the predictive value of DRU system for curve progression in braced female IS patients. Methods This was a consecutive longitudinal study including physically immature IS girls receiving standardized bracing treatment and regularly followed up every 3–6 months until brace weaning. The following data of each visit were collected: chronologic age, standing height, Cobb angle, spinal length, Risser sign, digital skeletal age (DSA) scores and DRU scores. The height velocity (HV), spinal growth velocity (SGV) and angle velocity (AV) of each visit were calculated. The correlation among radius stage, ulna stage, Risser sign, height, spinal length, HV, SGV and AV was studied. Results Forty braced IS girls with 349 longitudinal whole spine X-rays were reviewed. The average DRU scores at initial visit were R6.5 ± 1.1 and U4.5 ± 1.2 for radius and ulna, respectively. Both the radius stages between R5 and R8 and ulna stages between U3 and U6 indicated high SGV and high HV. The DSA scores were 402.1 ± 48.8 and 430.8 ± 44.4 at R7 and R8, respectively. The AV values were − 5.9 ± 12.4°/y and − 0.4 ± 1.5°/y at R5 and R6, which increased to 5.9 ± 17.3°/y, 3.1 ± 15.7°/y and 4.2 ± 12.2°/y at R7, R8 and R9, respectively. The DSA scores were 387.3 ± 65.7 for U5 and 432.9 ± 48.5 for U6, respectively. The AV values were − 3.1 ± 0.3°/y at U3, − 1.7 ± 9.3°/y at U4, 2.3 ± 16.1°/y at U5, 5.4 ± 15.5°/y at U6 and 4.4 ± 12.9°/y at U7. Conclusions Both distal radius and ulna scores correlate with the longitudinal growth potential, and thus, the DRU scoring scheme is an alternative predictor for growth potential and curve progression in girls with IS. Graphic abstract These slides can be retrieved under Electronic Supplementary Material.